2007
DOI: 10.1002/jcc.20722
|View full text |Cite
|
Sign up to set email alerts
|

IDEA: Interface dynamics and energetics algorithm

Abstract: IDEA, interface dynamics and energetics algorithm, was implemented, in FORTRAN, under different operating systems to mimic dynamics and energetics of elementary events involved in interfacial processes. The code included a parallel elaboration scheme in which both the stochastic and the deterministic components, involved in the developed physical model, worked simultaneously. IDEA also embodied an optionally running VISUAL subroutine, showing the dynamic energy changes caused by the surface events, e.g., occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(45 citation statements)
references
References 87 publications
2
43
0
Order By: Relevance
“…Finally, it has been found that, oppositely to what experimentally observed for the cis-but-2-ene/trans-but-2-ene gas-phase order of stability, several 52T systems containing cis-but-2-ene resulted more stable than the analogous systems involving trans-but-2-ene isomer adsorbed on the same acidic -OH sites, confirming the basis role played by the local steric hindrance, in driving molecular adsorption properties and surface reactivity in confined spaces [78][79][80][81][82].…”
Section: Quantum Chemical Models Of Acidic Sitessupporting
confidence: 72%
“…Finally, it has been found that, oppositely to what experimentally observed for the cis-but-2-ene/trans-but-2-ene gas-phase order of stability, several 52T systems containing cis-but-2-ene resulted more stable than the analogous systems involving trans-but-2-ene isomer adsorbed on the same acidic -OH sites, confirming the basis role played by the local steric hindrance, in driving molecular adsorption properties and surface reactivity in confined spaces [78][79][80][81][82].…”
Section: Quantum Chemical Models Of Acidic Sitessupporting
confidence: 72%
“…Therefore, specific local events are described with a high level of accuracy, and the approach is developed on a fully molecular-level base, revealing the inmost details of the process and suggesting criticisms to results obtained by more conventional modelling approaches [5,19].…”
Section: Introductionmentioning
confidence: 99%
“…Each of these elementary steps, including the null event, is characterized by an occurrence probability, which might be derived either from experimental or from quantum chemical (qc) calculation findings. Likewise, also the interactions between the various species adsorbed on the surface sites are characterized by adequate residence probabilities [5,9,10], which account for the steric hindrance of the adsorbed surface derivatives. Due to local interaction-potential changes, the surface-event occurrence probabilities are usually variable at the same time as the system is evolving.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations